Factors Contributing Door-to-Balloon Delays Among STEMI Patients in Low- and Middle-Income Countries (LMICs): Literature Review - I Gede Hendra kusuma Darmawan; Asti Melani Astari; Suryanto Suryanto (Lembaga Publikasi Ilmiah Nusantara, 2026)
Low- and middle-income countries (LMICs) bear a disproportionate burden of mortality from ST-Elevation Myocardial Infarction (STEMI), largely due to difficulties in meeting the recommended door-to-balloon (D2B) time of ≤90 minutes, a delay proven to increase in-hospital mortality. This review aims to identify and map the factors influencing door-to-balloon (D2B) delay in ST-Elevation Myocardial Infarction (STEMI) patients in low- and middle-income countries (LMICs). This study employed a literature review methodology to identify factors influencing door-to-balloon (D2B) delays in STEMI patients in low- and middle-income countries (LMICs). A systematic search following PRISMA guidelines was conducted in ProQuest, Google Scholar, and EBSCO for publications from 2021–2025 using PCC-based keywords related to LMICs, STEMI, reperfusion, and delay. The results of this review show that factors causing door-to-balloon (D2B) delay can be grouped into four main pillars. Internal hospital factors were the most dominant, followed by patient-related factors, pre-hospital system barriers, and external factors such as pandemics and conflicts that further prolonged delays. It is recommended to strengthen collective commitment and synergy among all stakeholders, including policymakers, hospital management, healthcare workers, pre-hospital personnel, and the community. Improvements should be implemented through a simultaneous, holistic approach to achieve significant, sustainable outcomes.